-7+ 5x = 10x-2? im not sure I know its -1, but im not sure how. -7 + 5x = 10x - 2 Since we need to get the unknowns on one side and the knowns on the other side and change their signs: 5x - 10x = 7 - 2 -5x = 5 x = -1 wait how did
Find the equation of the tangent line 5x^2+y^2=14 at (1,3). P.S: It's calculus. So far I know this much 10x+2y(dy/dx)=o -10x -10x ___________________ 2y(dy/dx)= -10x (dy/dx)= -10x/2y= -5x/y m= -5(1)/3= -5/3 y=mx+b 3= -5/3(1)+b
i was wondering if anyone could help me on this problem. expand: x^-2 (y^2 + 10x) z^3 (5x + 3z^-4) First one: x^-2 (y^2 + 10x) x^-2 is the same thing as 1/x^2. Therefore, we have this: 1/x^2 (y^2 + 10x) Multiply using the
Determine whether the point (1, 8) is a solution of the system 2x + 6y = 50 10x + 0y = 10 by substituting the point into each equation. So far I have: 2x=6y=50 y=50-2x 10x+10y=10 10x+0(50-2x)=10 10x+0=10 x=10 y=50-2x y=50-2(1)
Thanks Reiny, but I'm still lost. I understand how you multipled by 10X on the right to get 17x, but you went too fast on the left, and I have no idea how you got 10x^2-20 from the starting left side. Can you show each step?
Solve. 29x – 2(9x – 0.455) = 10x + 0.525 Give us you thinking on this so we can help you solve the equation. What is it you don't understand about solving this eqution? 29x –2(9x – 0.455) = 10x + 0.525 29x – 18x – 0.91